Review on the Biological Activities and Phytochemistry of the Genus Satureja - Kartal M.; Yıldız A. N.; İnal E.; Kiraz Kınıoğlu B.; Dirmenci T.; Gören A. C. (My University, 2025)
The genus of Satureja species belongs to the Lamiaceae family and has been used as culinary spice and condiment as well as in traditional medicine for the treatment of a variety of diseases such as gastrointestinal system disorders including cramps, nausea, indigestion, and diarrhea and respiratory system disorders, skin disorders, pain and inflammation. The genus is represented by 61 taxa worldwide, and 17 taxa are distributed in Türkiye. This paper reviews biological activity and phytochemical constituents of Satureja species. The related scientific and books, journals, articles and Pubmed, Scopus, Science Direct and Google Scholar databases were searched using the keyword \"Satureja\" related to the studies on the phytochemistry, secondary metabolites, essential oil, volatiles, phytochemisrty and/or biological activities were evaluated and reviewed. As a result of this current review, current data on the Satureja genus was assessed mainly for various biological activities. Especially the anticholinergic, anti-antioxidant, cytotoxic, antimicrobial, anti-inflammatory, analgesic/antinociceptive, larvicidal, and insecticide activities of the genus are remarkable. However, only a limited number of the current literature focused on the isolated active compounds. As a result, the genus Satureja presents a significant potential as a natural resource for the development of agricultural products for new pharmaceuticals, cosmetics, veterinary products, and foods of different sectors. New research and in vivo bioactivity evaluations may open new avenues for the valorisation of Satureja preparations especially in the health and cosmetic industries.
Keywords: Eczacılık; Meslek Bilimleri; Farmakognozi; Sağlık Bilimleri; Pharmacology and Therapeutics; Professional Sciences; Pharmacognosy; Health Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Farmakoloji ve Toksikoloji; Farmakoloji ve Eczacılık; Clinical Medicine (Med); Life Sciences (Life); Pharmacology & Toxicology; Pharmacology & Pharmacy; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences